МАТЕМАТИКА И МАТЕМАТИЧЕСКО ОБРАЗОВАНИЕ - Jancheski, Metodija (My University, 2009)
The paper consists of four general parts. After a brief review of the worldwide responsible institutions for teachers’ trainings in the framework of their continuous education, the paper will discuss the characteristics of national teachers’ training programmes. Some of the educational systems prefer pedagogical skills, some of them prefer ICT skills, but the best solution is in their integration. The ICT-enhanced skills are also recognized as synergy between, so called, soft skills and ICT skills. Follows examples of ICT support services in some European schools, as well as, the defined main roles, and actors. The last part discusses the different experiences of assessment and evaluation the ICT competencies of teachers and the variety of teachers’ ICT certification. The paper includes the Macedonian experience in the field of teachers’ continuous education which is on the main crossroad taking into account the current mass computerization of the Macedonian schools. In each chapter, the author gives some proposals for improvement the use of ICT in Macedonian schools, as well as, for increasing the teachers’ ICT skills and their implementation.
MATHEMATICS AND EDUCATION IN MATHEMATICS